LA SATISFACCIÓN DE LOS JUBILADOS POR LA ATENCIÓN MÉDICA RECIBIDA EN EL HOSPITAL DEL DÍA CENTRAL IESS- LOJA, PERIODO 2016 - Matute Cevallos, Adriana Isabel (2017)
The interest in the quality and satisfaction of the medical care has its origin in the discomfort expressed by the users of the Public Health Services, and also in the desire to reduce the inequality in the Health System of the different social groups. This is why the present research aims to determine the level of satisfaction of retirees for the medical care received at the Hospital of the central day IESS - Loja, period 2016; For this, an analysis of the target population (retired) was carried out, and after determining the sample, the qualitative and quantitative methods and techniques were applied, which allowed to collect information on the expectations and perceptions of the retired users, making Use of the Servqual method; The same that takes into account five dimensions of quality as they are; Tangible elements (Aspect of Physical Facilities, Equipment, Personnel and Communication Materials), Reliability (Ability to execute Promised Service Reliably and Carefully), Responsiveness (Willingness and Will of Employees to Assist Customer and Provide Service), Safety (Knowledge and Attention shown by Employees and their Skills to Inspire Credibility and Trust) and Warmth or Empathy (Individualized Care offered by Businesses to users); These five dimensions helped to determine the level of satisfaction from the perspective of the retired user, obtaining results of dissatisfaction in two dimensions as they are; Reliability and responsiveness specifically when taking shifts through the call center, waiting time between sign-in and medical consultation and number of specialists; With these results we proceeded to make an improvement plan that will help raise the level of satisfaction of retired users.